Influencer: Sumber Daya Promosi yang Ramah Wisatawan Milenial - Siryayasa, I Nyoman; Sudarmi, Sudarmi; Ridwan, Masri; Salim, Muhammad Arfin Muhammad; Rahmayanti, Firda (Universitas Nahdlatul Ulama Blitar, 2024)
Research was carried out to understand the role of social media and Influencers on tourist interest in visiting Enrekang Regency. This research approach is quantitative-descriptive based on the philosophy of positivism. Data collection used research instruments; data analysis was quantitative-statistical. Probability sampling using simple random sampling technique to obtain samples. This research consisted of 60 respondents. The data presented shows that Influencers are parties who have a large number of followers and play an important role in promotion using social media such as Instagram, YouTube, Twitter and Facebook to promote tourist attractions. The research results prove that there is a significant relationship between social media and interest in visiting and being able to explain variables with an influence of 74% and the Influencer variable of 81%. Millennial tourists are most interested in visiting Enrekang Regency as much as 20% with the main aim being tourist attractions that can provide experiences through sightseeing/panorama activities, photography, mini restaurants, camping grounds, creative art, pine forests, game rides. Real collaboration is needed between the relevant government, tourist attraction managers, influencers and millennial tourists to create Enrekang as a tourist destination.Â